Internal Control And Fraud Prevention In Online Business In Indonesia - Arifia Yasmin; Anita Karunia; Harnum Hanifah (Politeknik Negeri Madiun, 2023)
It is undeniable that online business in Indonesia has gone a rapid development, which is inseparable from internet technology development. Nonetheless, there is assurance internal controls that are effective and sufficient are applied in online businesses. Given the fraud problems in online business, internal control is certainly demanded. This paper aims to investigate information in online business and to determine the consequence of internal control of online business on fraud prevention and detection in Indonesia economy development, particularly online business. This research employed qualitative descriptive method using analysis, data as well as taking advantage of prevailing theories as underpinning information. Secondary data sources used are research journals and are based on the